Prevalence of postpartum-abnormal glucose tolerance (P-AGT) and its associated factors among women with gestational diabetes mellitus (GDM) in Klang, Selangor / Shafawati Akmal Adam - Adam, Shafawati Akmal (2023)
Introduction: Women with gestational diabetes mellitus (GDM) have a risk to develop diabetes at least seven times higher than other women. The study aimed to determine the prevalence of postpartum-abnormal glucose tolerance (P-AGT), the level of knowledge on GDM and the associated factors for P-AGT among postpartum women with GDM attending public health clinics in Klang. Methods: This cross-sectional study used convenience sampling and was conducted among GDM women attending the oral glucose tolerance test (OGTT) at six to 12 weeks postpartum. Sociodemographic factors, clinical characteristics, knowledge about GDM (using a validated questionnaire, GDMKQ) and postpartum OGTT results were collected. Results: The study included 439 participants. The majority were below the age of 35 years old (71.8%), of Malay ethnicity (82.7%), and demonstrated adequate knowledge of GDM (92.9%). The prevalence of P-AGT was found to be 28.9% (95% CI:24.7, 33.4). Multiple logistic regression analysis showed gestational age upon GDM diagnosis <24 weeks (aOR: 1.85, 95% CI: 1.17, 2.92; p = 0.009), abnormal 2-hour postprandial (2HPP) level (>7.8mmol/L) upon GDM diagnosis (aOR: 2.95, 95% CI: 1.74, 5.00; p < 0.001) and first-degree family history of diabetes (aOR: 1.55, 95% CI: 1.01, 2.39; p = 0.047) were significantly associated with P-AGT. Conclusion: This study revealed higher prevalence of P-AGT compared to previous local studies. Targeted monitoring and management strategies are crucial, especially for women diagnosed with GDM before 24 weeks of gestation, those who had abnormal 2HPP level upon GDM diagnosis and those with first-degree family history of DM to prevent the occurrence of P-AGT.